Optimizing Public Service through Innovative Talent Management Strategies for Public Officials: A Case Study in the Riau Islands Province - Sholeh, Chaereyranba; Firman, Firman; Abdul Malek, Jalaluddin; Kartini, Novang Cahya Sri (Department of Public Administration, 2024)
Talent Management is a crucial element for public organizations, which includes absorbing, identifying, and retaining civil servants who have outstanding talents in each organization and make a significant contribution to the progress of public organizations to create excellent public services. A talent management model in the public sector, especially at the local government level, is needed because approximately 80% of civil servants are placed in the regions, and the dynamics of the bureaucratic environment are more dynamic and complex. The Riau Archipelago Province is one of the areas that has implemented a merit system, but the career pattern could have gone better. This study aims to analyze strategies for implementing Talent Management to accelerate bureaucratic reform and manage the capacity of civil servants in the Provincial Government of the Riau Archipelago. This research method uses a qualitative exploratory case study methodology. The results of this study show that the Riau Islands Provincial Government has not implemented Talent Management for civil servants by the mandate of the PAN RB Ministerial Regulation Number 3 of 2020, which is currently in the preparation stage of regulations in the form of a Governor's Regulation concerning the Management of Civil Servants Talents in the Islands Provincial Government Riau. Therefore, aspects of career development in the merit system must be a significant concern so that the Riau Islands Provincial Government can meet the desired targets.